Cytosolic and mitochondrial Ca2+ concentrations in primary hepatocytes change with ageing and in consequence of an mtDNA mutation. (September 2019) - Niemann, Jan; Zehm, Cindy; Waterstradt, Rica; Tiedge, Markus; Baltrusch, Simone
Graphical abstract: Highlights: Glucose-induced cytosolic (but not mitochondrial) Ca 2+ influx increased with ageing in hepatocytes of C57BL/6NTac mice. In hepatocytes of conplastic C57BL/6NTac-mt NODLtJ mice glucose-induced mitochondrial Ca 2+ influx declined with ageing. A reduction of the MICU1/MCU expression ratio and a decline in MCUR1 expression was noted only in ageing C57BL/6NTac-mt NODLtJ mice. Colocalisation of MICU1 with the hyper-fused mitochondrial network of C57BL/6NTac-mt NODLtJ mice was detectable. Abstract: Mitochondrial Ca 2+ flux is crucial for the regulation of cell metabolism. Ca 2+ entry to the mitochondrial matrix is mediated by VDAC1 and MCU with its regulatory molecules. We investigated hepatocytes isolated from conplastic C57BL/6NTac-mt NODLtJ mice (mtNOD) that differ from C57BL/6NTac mice (controls) by a point mutation in mitochondrial-encoded subunit 3 of cytochrome c oxidase, resulting in functional and morphological mitochondrial adaptations. Mice of both strains up to 12 months old were compared using mitochondrial GEM-GECO1 and cytosolic CAR-GECO1 expression to gain knowledge of age-dependent alterations of Ca 2+ concentrations. In controls we observed a significant increase in glucose-induced cytosolic Ca 2+ concentration with ageing, but only a minor elevation in mitochondrial Ca 2+ concentration. Conversely, glucose-induced mitochondrial Ca 2+ concentration significantly declined with ageing in mtNOD mice, paralleled by a slight decrease in cytosolic Ca 2+ concentration. This was consistent with a significant reduction of the MICU1 to MCU expression ratio and a decline in MCUR1. Our results can best be explained in terms of the adaptation of Ca 2+ concentrations to the mitochondrial network structure. In the fragmented mitochondrial network of ageing controls there is a need for high cytosolic Ca 2+ influx, because only some of the isolated mitochondria are in direct contact with the endoplasmic reticulum. This is not important in the hyper-fused elongated mitochondrial network found in ageing mtNOD mice which facilitates rapid Ca 2+ distribution over a large mitochondrial area.